Taboo Words in 21 Jump Street Movie - Desak Gede Yulia Kusumaningsih (RETORIKA: Jurnal Ilmu Bahasa, 2019)
The aim of this research is to classify the kinds, functions of taboo words, and the factors which cause the characters use the taboo words in the movie. Data were analyzed by using taboo words theory by Michael Swan and factors underlying cursing theory by Timothy Jay. The data were taken from 21 Jump Street movie. In this research, library research method is used in analyzing taboo words in 21 Jump Street movie. The procedures of the research are: first, the movie is watched and the topics for the paper are found. Second, the theory in the books and internet are found. Third, the movie script is searched and the taboo words are classified. The last, the taboo words in 21 Jump Street movie are discussed and analyzed by using Michael Swan and Timothy Jay theories. Based on the result of the analysis, there are three kinds of taboo word that found in 21 Jump Street movie: (1) religion, (2) private parts of the body and sexual activity, and (3) lavatory. Private parts of the body and sexual activity has the biggest number of occurrence, while the smallest number of taboo words’ kind is religion. There are six functions of using taboo words that I found in the movie. They are: insult, exclamation of annoyance, surprised question, exclamation of surprise, emphasize an emotion, and miscellaneous. The most appeared function is to insult and the smallest is as a surprised question. Furthermore, the reason of the characters in 21 Jump Street movie to used taboo words are based on the situation and context. On the other hand, there are three reasons of using taboo words which found in the movie, such as psychological condition, social class, and ethnic group. Psychological condition has the biggest number of occurrence, while the smallest is social class.